2004
DOI: 10.1210/jc.2003-031631
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens Are Potent Inhibitors of Estrogen Sulfation: Implications for Breast Cancer Risk and Treatment

Abstract: We investigated the ability of 37 flavonoids and flavonoid sulfoconjugates, including some abundant dietary constituents, to act as substrates and/or inhibitors of the sulfotransferase and sulfatase enzymes that interconvert active estrogens and inactive estrogen sulfates in human tissues. The enzymes studied include estrogen sulfotransferase, the thermostable phenolsulfotransferase that acts on a range of substrates including estrogens; steroid sulfatase; and two related enzymes, monoamine phenolsulfotransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 47 publications
4
76
0
1
Order By: Relevance
“…Presumably, 7,8-dihydroxyflavone might not inhibit aromatase, either. In addition to the activity described above, 7,8-dihydroxyflavone also has been shown to inhibit aldehyde dehydrogenase and estrogen sulfotransferase in vitro with K i values of 35 μM and 1-3 μM, respectively (23,24). However, these actions have not been confirmed in animals.…”
Section: Kinases a Binding Assay Demonstrated That Increasing Concenmentioning
confidence: 97%
“…Presumably, 7,8-dihydroxyflavone might not inhibit aromatase, either. In addition to the activity described above, 7,8-dihydroxyflavone also has been shown to inhibit aldehyde dehydrogenase and estrogen sulfotransferase in vitro with K i values of 35 μM and 1-3 μM, respectively (23,24). However, these actions have not been confirmed in animals.…”
Section: Kinases a Binding Assay Demonstrated That Increasing Concenmentioning
confidence: 97%
“…There are a number of reports indicating that various flavonoids, such as hexamethoxyflavone, tangeretin and silybin are potent inhibitors of UGTs in vitro, with IC 50 values \1 lM [72,83,84]. Similarly, a number of flavonoids (fisetin, galangin, quercetin, myricetin, chrysin, kaempferol, apigenin and genistein) have been identified in vitro as potent inhibitors of various SULTs [15,26,52], but as with the UGTs, it is not known whether such in vitro interactions translate into significant in vivo effects.…”
Section: Inhibition Of Phases 1 and 2 Enzymes By Polyphenolsmentioning
confidence: 99%
“…Nishiyama et al [44] reported that daidzein and genistein are predominantly sulfated by SULT1A1 and SULT1E1, respectively in humans and inhibit the sulfation of the endogenous substrate, beta-estradiol. Harris et al [41] demonstrated that equol, genistein and daidzein inhibited human SULT1E1 in that order of potency. Human SULT1A1, another sulfotransferase involved in the sulfation of estrogens, also uses daidzein as a substrate, and is inhibited by both daidzein and genistein at similar concentrations [38].…”
Section: Enzymes and Metabolic Pathwaysmentioning
confidence: 99%
“…Genistein and daidzein can inhibit and induce various enzymes involved in sex steroid metabolism [37][38][39][40][41][42]. They inhibit steroid metabolizing enzymes such as 5-alpha reductase [29], aromatase [7,39] and 17-β hydroxysteroid dehydrogenase Type 1 [37].…”
Section: Enzymes and Metabolic Pathwaysmentioning
confidence: 99%